Premenstrual Syndrome dan Prestasi Belajar Mahasiswi - Astuti Anggraini, Tyasning Yuni (Universitas Jenderal Achmad Yani Yogyakarta, 2012)
The objective of research is to evaluate the effect of Premenstrual Syndrome on the Female Studentsâ Learning Achievement in DIII Midwifery Study Program of STIKES A. Yani Yogyakarta. This study employed a qualitative method research using a case study design and is descriptive in nature. The subject of research was the female students who encounter premenstrual syndrome. The Shortened Premenstrual Assessment Form (SPAF) instrument was given in semester II to 212 female students, so that it can be found 11 female students encountering premenstrual syndrome.From the FGD (Focus Group Discussion) result and in-depth interview, it can be found the physical and psychological changes in the female students developing premenstrual syndrome that can affect the behavior change occurrence. The conclusion of research is that there is physical, psychological and behavior changes in the female students developing premenstrual syndrome but with their high motivation make their majority learning achievement very satisfactory. Keywords: Premenstrual Syndrome and learning achievement.